Managing the Versioning Decision over an App's Lifetime. (November 2021) - Lee, Seoungwoo; Zhang, Jie; Wedel, Michel
The authors investigate app publishers' decisions to offer free, paid, or both versions of an app over an app's lifetime by taking into account the interplays between the demand for the free and paid versions and publishers' consideration of future profit streams. Their empirical analyses are based on a comprehensive model of publishers' versioning decisions calibrated on a data set of 584 top-downloaded apps on Google Play. They find contemporaneous cannibalization but positive intertemporal cross-effects on new users' demand between the two versions. In addition, the free version's active user base and in-app purchase and advertising revenues are reduced by the presence of a paid version, but not vice versa. Among the three options, offering the paid version first is the most common optimal launch strategy and applies to 40% of apps in the data. The evolutionary patterns of optimal versioning decisions vary by app category and are related to apps' abilities to monetize different revenue sources. This study provides insights on how to strategically manage the versioning decision over an app's lifetime and shows how publishers can make their free version apps more profitable via the deployment or elimination of the paid version.